The impact of preventive fogging on entomological parameters in a university campus in Malaysia - Adnan, Ruhil Amal; Osman, Malina; Awang Hamat, Rukman; Unyah, Ngah Zasmy; Abdullah, Wan Omar; Mohtarrudin, Norhafizah (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2011)
Preventive fogging is defined as space spraying of insecticide against mosquitoes in order to prevent outbreak of mosquito borne infection. Despite provision of various preventive andcontrol activities against dengue and chikungunya infection by Ministry of Health Guideline, the detail on preventive fogging has not yet specified. However, this has been adopted by certain institutions as part of the routine strategies against dengue outbreak. A study on preventive fogging was conducted in one of the hostels in Universiti Putra Malaysia. The research was done for 16 weeks in which one routine fogging activity was done at the mid period of study. The main objectives of this study were to determine the effectiveness of preventive fogging activities against Aedes mosquitoes and to identify the distribution and abundance of Aedes mosquitoes in the area. Method: The fogging activity was carried out by the management staff as part of their preventive measures in the student hostels. Ovitrap was used as an indicator to monitor the impact of fogging activity and its continuous surveillance was monitored weekly. The ovitraps were placed indoors and outdoors. Species identification was carried out in the laboratory. The SPSS program was used to analyse the statistical data on the effectiveness of fogging activity. Larval count (indoors and outdoors) and ovitrap index (OI) readings were identified as ovitrap surveillance data for statistical analysis. Results: The results showed that Aedes albopictus was the only species of the genus Aedes found in this hostel. The area had been highly infested by Ae. Albopictus as indicated by high Ovitrap Index ranging between 48.33% to 90.00%. The mean (SD) of Ovitrap Index was reduced from 71.67% (12.73%) (before the preventive fogging), to 69.42% (14.40%) (after the fogging). Overall reduction in mosquito and larval density was also observed between pre and post fogging activity in this study. Conclusion: The implementation of preventive fogging has favourably reduced the dengue vector population up to 5 weeks after the introduction of preventive fogging. However, sole dependency on preventive fogging may lead to insecticide resistance. Revisiting the policy on preventive fogging; and identifying it as an additional tool for preventing dengue infection in higher learning institutions are recommended.